2022
DOI: 10.1001/jamanetworkopen.2022.40132
|View full text |Cite
|
Sign up to set email alerts
|

Association of National Football League Fan Attendance With County-Level COVID-19 Incidence in the 2020-2021 Season

Abstract: ImportanceThe 2020-2021 National Football League (NFL) season had some games with fans and others without. Thus, the exposed group (ie, games with fans) and the unexposed group (games without fans) could be examined to better understand the association between fan attendance and local incidence of COVID-19.ObjectiveTo assess whether NFL football games with varying degrees of in-person attendance were associated with increased COVID-19 cases in the counties where the games were held, as well as in contiguous co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…Despite the strength of the study, several questions remained unresolved. The findings in the study by Kurland et al findings do not agree with those of Toumi et al, who found no association with fan attendance and increased COVID-19 cases. The reasons for this discordance—whether from methodological differences, the broader geographic sweep, or larger number of games including those in the postseason—is unknown.…”
contrasting
confidence: 58%
See 3 more Smart Citations
“…Despite the strength of the study, several questions remained unresolved. The findings in the study by Kurland et al findings do not agree with those of Toumi et al, who found no association with fan attendance and increased COVID-19 cases. The reasons for this discordance—whether from methodological differences, the broader geographic sweep, or larger number of games including those in the postseason—is unknown.…”
contrasting
confidence: 58%
“…This study is similar in design to a previous report by Toumi and colleagues, but Kurland and colleagues use a broader base of National Football League games and consider a wider geographic area. As a result, this approach has the potential to capture the outcomes of not only the game itself, but ancillary activities surrounding fan participation.…”
mentioning
confidence: 89%
See 2 more Smart Citations